Fabrication and characterization of electrically conductive copper coated poly(p-phenylene-2, 6-benzobisoxazole) yarn. (14th October 2020) - Geng, Liang; Zhu, Puxin; Guo, Ronghui; Lai, Xiaoxu; Xiao, Hongyan; Ren, Erhui; Zhou, Mi
ABSTRACT: In order to develop conductive materials with high tensile strength and high Young's modulus, copper was deposited on the surface of Poly( p -phenylene- 2, 6-benzobisoxazole) (PBO) yarn by electroless plating. Copper coated PBO yarns were characterized by SEM, XRD and XPS. Weight gain rate and electrical resistivity of copper coated PBO yarns were measured. The result shows that the copper layer is deposited uniformly and densely with high purity. The copper coated PBO yarn not only possesses excellent mechanical strength with a tenacity of 121.27 cN/tex but also exhibits excellent electrical conductivity with the resistivity of 4.20 × 10 −7 Ω·m under 3200cN tension force. In addition, the copper coated yarns can generate heat and the temperature of copper coated yarn maintains at 60°C with only 1.8 V. The result indicates that copper coated PBO yarn is promising conductive material. Therefore, copper coated PBO yarn can be applied in fields such as flexible sensor, e-textile and flexible heating pads.